Conflict, educational attainmnet and structural transformation: "La Violencia" in Colombia (2015)
We examine the long-term impact of violence on educational attainment, with evidence from Colombia's La Violencia. Individuals exposed to violence during, and especially before, their schooling years experience a significant and economically meaningful decrease in years of schooling. This impact has consequences beyond human capital accumulation: exposed cohorts engage in activities with less human capital content. Violence thus influenced aggregate development - particularly the process of structural transformation, in which some sectors gain prominence as income increases. The effects result not so much from the direct destruction of physical infrastructure, but from affected households' responses to the hardships of conflict.